1993
DOI: 10.1128/jb.175.2.557-560.1993
|View full text |Cite
|
Sign up to set email alerts
|

The Helicobacter pylori 19.6-kilodalton protein is an iron-containing protein resembling ferritin

Abstract: The gastric pathogen Helicobacter pylori has been shown to produce a 19.6-kDa protein with apparent binding activity for erythrocytes, human buccal epithelial cells, and laminin. In this report we demonstrate that it is an iron-binding protein, resembling ferritin both structurally and biochemically. Also, because its binding activity for laminin, erythrocytes, and buccal cells was abolished by low concentrations of Tween 20, binding is likely nonspecific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 22 publications
1
60
0
2
Order By: Relevance
“…There exists some speculation that the roles of the mammalian and bacterio-type ferritins may in fact be somewhat different. This view is supported by the recent isolation of a mammalian-type ferritin from E. coli, an organism which also contains Bfr [13,14] as well as from Helicobacter pylori [15].…”
Section: Introductionmentioning
confidence: 93%
“…There exists some speculation that the roles of the mammalian and bacterio-type ferritins may in fact be somewhat different. This view is supported by the recent isolation of a mammalian-type ferritin from E. coli, an organism which also contains Bfr [13,14] as well as from Helicobacter pylori [15].…”
Section: Introductionmentioning
confidence: 93%
“…Doig et al reported that approximately 20% of the total amount of ferritin-like protein was detected in membrane fraction and the majority of the protein was localized in the cytosolic fraction in Helicobacter pylori. 24) If the distribution of ferritin-like protein in MS-1 cell is similar to that observed in H. pylori, the Raman spectrum of …”
mentioning
confidence: 99%
“…However, it has been shown before that it is not advisable to draw conclusions from cellular fractionation studies alone. For example, Doig et al [21] observed 44% of the ferritin of H. pylori to be in the membrane fraction despite electron microscopy studies revealing it to be exclusively cytoplasmic [51]. Thus, additional data to support the fractionation studies are required.…”
Section: Conditionsmentioning
confidence: 97%
“…It is the presence of haem in purified Alternative bacterial iron-storage systems to bacterioferritin exist. Fenitin of the non-haem type, with a relatively high sequence similarity to animal fenitin, has been isolated from Helicobacter pylori [21] and Bacteroides fragilis [22], and its gene has been cloned from E. coli [23]. Furthermore, the 57Fe Mossbauer spectroscopy study of intact E. coli cells reported by Matzanke et al [24] clearly identified two ironrich species present in greater quantity than bacterioferritin that might constitute a novel iron-storage system.…”
mentioning
confidence: 99%